Fertility model and female labour force participation in selected ASEAN countries - Abdullah, Norehan; Abu Bakar, Nor'Aznin; Abdullah, Hussin (2013)
This paper tends to investigate the ambiguous relationship between fertility and women’s labour force participation in the case of Malaysia and other selected Asian countries such as Singapore, Thailand, Indonesia, the Philippines and Vietnam.Using a panel of observations for the period 1995 to 2009, this study examines the correlation and panel causality effect between fertility rate, female labour force participation, and other fertility factors.The panel analysis was done on the six selected ASEAN countries (ASEAN-6), as well as for each of the individual country. This study found that there is mixed correlation between the regression variables in ASEAN countries but none of them have a strong correlation.The results on causality tests show that primary education, health expenditure, life expectancy at birth, labour participation rate, and self-employed - female do not granger-cause fertility rate in all six ASEAN countries.However there is a unidirectional causality which runs from fertility rate to education primary, life expectancy at birth and labour participation rate.